Corona Discharge Model for Transmission Lines by Lumped Elements - Costa, E. C. M.; Kurokawa, S. [UNESP]; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper shows the insertion of corona effect in a transmission line model based on lumped elements. The development is performed considering a frequency-dependent line representation by cascade of pi sections and state equations. Hence, the detailed profile of currents and voltages along the line, described from a non-homogeneous system of differential equations, can be obtained directly in time domain applying numerical or analytic solution integration methods. The corona discharge model is also based on lumped elements and is implemented from the well-know Skilling-Umoto Model.
Keywords: Corona discharge; lumped elements; transmission line model; state equations